Hematopoietic Cell Transplantation for Chronic Granulomatous Disease in Japan - Yanagimachi, Masakatsu; Kato, Koji; Iguchi, Akihiro; Sasaki, Koji; Kiyotani, Chikako; Koh, Katsuyoshi; Koike, Takashi; Sano, Hideki; Shigemura, Tomonari; Muramatsu, Hideki; Okada, Keiko; Inoue, Masami; et al. (Frontiers in Immunology, 2020)
Hematopoietic cell transplantation (HCT) is established as a curative treatment for severe chronic granulomatous disease (CGD). However, outcomes of HCT for CGD in Japan had not been precisely reported. We evaluated the outcome of HCT for CGD in Japan by means of a nationwide survey. A total of 91 patients (86 males and 5 females) with CGD who received HCT between 1992 and 2013 was investigated. Their median age at HCT was 11 years (0-39). Sixty-four patients had X-linked CGD caused by CYBB gene mutations, 13 had autosomal recessive CGD (7 CYBA and 6 NCF2), and 14 were genetically undetermined. Seventy patients are still alive at a median follow-up of 38.9 (3.7-230) months. Three-year OS and EFS was 73.7% and 67.6%, respectively. Twenty-one patients died mainly from transplant-related mortality. The cumulative incidence of grade II to IV acute GVHD and extensive chronic GVHD was 27.2% and 17.9%, respectively. Risk factors for EFS after HCT for CGD were age >30 years (P<0.01), non-CYBB gene mutations (P<0.01) and CBT (P<0.01). Regarding the reduced intensity conditioning (RIC) regimen, risk factors for EFS included anti-thymocyte globulin (P=0.048) and not using low-dose irradiation therapy (P<0.01), in addition to the preceding risk factors. We report outcomes of HCT for CGD in Japan. Future studies are needed to improve such outcomes, especially for patients harboring non-CYBB gene mutations and suffering from adult CGD. A RIC regimen including low-dose irradiation may be a good option to explore further.